Grudge leadership : clarity vs obscurity. - Hamzah, Mohd Sahandri Gani; Abdullah, Saifuddin Kumar (Eurojournals, 2009)
This paper is a venture and an explanation towards recent leadership polls which has been an issue frequently debated within lower level leaders. Collected facts and evidences are one of the simple ethnographic study processes in a few subordinate leadership groups in the line of education management. The information is collected by a few series of chatting, socializing and assimilating facts and elaborations by unwary respondents who has stressed on some parts of their conversation repeatedly. The trustworthiness of the results is analyzed to through cross-sectional checking to standardize the results to be reported. Overall the leaders have a key performance index which fulfils the minimum needed level. The grudge based leadership involves frequent detection of leaders' weaknesses and minor mistakes as shown in the conceptual framework. Because of that, they always received new groups who supported objectives such as mismatch, suppression, denying of other people's rights, acting roughly, providing stress, hating, neglecting, rejecting, discrimination, causing trouble and isolating others without reason. This environment became dominant to the point of causing dissatisfaction within the lower level leaders and officers. This practice implies the existence of interactional understanding gaps which are unhealthy as these leaders are the ones who will succeed to the present leadership. This situation has also created a new space for new leaders. A special committee has to be set up to detect the professional leadership bias through mechanisms of psychometric and personality evaluation for determining the continuity from the aspects of practice, privacy and effectiveness in leadership management.